Structural change with public educational expenditure: Evidence from the People's Republic of China - Xun Zhang (Asian Development Bank Institute (ADBI), 2018)
This paper represents an early attempt to analyze the comprehensive relationship between public educational expenditure and structural change, which is often measured by labor transfer from agricultural sector to industrial sector in developing economies. I construct a two-sector general equilibrium model, showing that in the short term, public educational expenditure mainly crowds out industrial capital accumulation and thus temporarily hinders structural change, while there is an inverted-U relationship between them in the long run, as public educational expenditure helps reduce the educational cost of rural residents permanently. The People's Republic of China's (PRC) hukou system provides appropriate data to empirically identify this comprehensive relationship. The empirical evidence confirms the theoretical interpretations when I control for confounding factors, take the endogeneity of public educational expenditure into account, and investigate the mechanisms behind the relationship. The PRC's current level of public educational expenditure is still far from its optimal value, as indicated by the inverted-U relationship with structural change, suggesting that the PRC should increase spending on public education, especially for rural residents.
Keywords: I28; O11; O15; 330; public educational expenditure; structural change; crowding-out effect; human capital; People's Republic of China (PRC)